Laboratory confirmed miltefosine resistant cases of visceral leishmaniasis from India. Issue 1 (December 2017) - Srivastava, Saumya; Mishra, Jyotsna; Gupta, Anil; Singh, Amit; Shankar, Prem; Singh, Sarman
Abstract Background Miltefosine unresponsive and relapse cases of visceral leishmaniasis (VL) are increasingly being reported. However, there has been no laboratory confirmed reports of miltefosine resistance in VL. Here, we report two laboratory confirmed cases of VL from India. Methods Two patients with VL were referred to us with suspected VL. The first patient was a native of the VL endemic state of Bihar, but residing in Delhi, a VL non-endemic area. He was treated with broad-spectrum antibiotics and antipyretics but was unresponsive to treatment. The second patient was from Jharkhand state in eastern India (adjoining Bihar), another endemic state for VL. He was refractory to anti-leishmanial treatment, which included administration of miltefosine. Following investigation, both patients were serologically positive for VL, and blood buffy coat from both patients grewLeishmania donovani . The isolates derived from both cases were characterized for their drug susceptibility, genetically characterised, and SNPs typed forLdMT andLdROS gene expression. Both patients were successfully treated with amphotericin B. Results The in vitro drug susceptibility assays carried out on both isolates showed good IC50 values to amphotericin B (0.1 ± 0.0004 μg/ml and 0.07 ± 0.0019 μg/ml). One isolate was refractory to SbIII with an IC50 of > 200 μM while the second isolate was sensitive to SbIII with an IC50 of 36.70 ± 3.2 μM. However, in both the isolates, IC50 against miltefosine was more than 10-fold higher (> 100 μM) than the standard strain DD8 (6.8 ± 0.1181 μM). Furthermore, genetic analyses demonstrated single nucleotide polymorphisms (SNPs) (354 Tyr↔Phe and1078 Phe↔Tyr) in theLdMT gene of the parasites. Conclusions Here, we document two laboratory confirmed cases of miltefosine resistant VL from India. Our finding highlights the urgent need to establish control measures to prevent the spread of these strains. We also propose thatLdMT gene mutation analysis could be used as a molecular marker of miltefosine resistance inL. donovani .